Targets and Patented Drugs for Chemotherapy of Chagas Disease in the Last 15 Years-Period - Duschak, Vilma G (2016)
Fil: Duschak, Vilma G. ANLIS Dr.C.G.Malbrán. Instituto Nacional de Parasitología; Argentina.